2018
DOI: 10.1177/1557988318799163
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Bisphenol A Levels and Male Fertility

Abstract: Bisphenol A (BPA) is a high-production volume industrial chemical found in many consumer products. BPA is a suspected potent endocrine disruptor, with endocrine-disrupting properties demonstrated in animal studies. Few human studies have examined bisphenol A exposure in relation to male fertility and, results are divergent. The aim of the study is to examine the associations between urinary BPA concentration and male fertility. Bisphenol A urinary concentrations were measured using gas chromatography coupled w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 30 publications
1
44
1
1
Order By: Relevance
“…Nevertheless, the presented study did not highlight any statistically significant link between the urinary levels of BPA and alterations of the parameters of seminal fluid, as conversely documented in various literature studies. This could be due to the particularly reduced levels of BPA herein recorded, on average 0.24 ± 0.43 µg/g creatinine, compared to those identified in the literature with values two [80] to ten [34] or twenty times higher [40].…”
Section: Discussioncontrasting
confidence: 49%
See 2 more Smart Citations
“…Nevertheless, the presented study did not highlight any statistically significant link between the urinary levels of BPA and alterations of the parameters of seminal fluid, as conversely documented in various literature studies. This could be due to the particularly reduced levels of BPA herein recorded, on average 0.24 ± 0.43 µg/g creatinine, compared to those identified in the literature with values two [80] to ten [34] or twenty times higher [40].…”
Section: Discussioncontrasting
confidence: 49%
“…According to Lassen et al [33] the association between BPA levels and reproductive hormones would support an anti-androgenic effect with deleterious consequences on motile spermatozoa (−6.7%, confidence interval-CI −11.76/1.63 95%), data confirmed also by Radwan et al [34].…”
mentioning
confidence: 53%
See 1 more Smart Citation
“…In another study on 191 Czech men with infertile marriages, seminal BPA, but not plasma BPA, levels were negatively associated with sperm concentration, sperm count, and, to a lesser extent, normal sperm morphology (118). More recently, Radwan et al (119) reported that urinary concentration of BPA in 315 men with normal sperm concentration according to the WHO 2010 criteria (124) was negatively associated with sperm motility and positively associated with the percentage of sperm sex chromosome disomy. Finally, in a recent report on a preconception cohort of 161 men without known subfertility, higher urinary BPA concentrations were found in the group of men with abnormal sperm tail morphology, whereas no association was found with sperm count, and no information was provided about other semen parameters (121).…”
Section: Effects On Semen Quality and Reproductive Outcomes: Evidencementioning
confidence: 98%
“…Due to the obvious lack of controlled clinical trials investigating the effects of BPA on human male fertility, information is largely inferred from findings of observational epidemiological studies that, with a few exceptions, used semen quality as a surrogate endpoint, producing divergent results likely due to heterogeneity in the extent of BPA exposure, sample sizes, type of population, and enrollment setting ( Table 1). Some studies included men from the general population (112)(113)(114)(115), others included men attending fertility clinics with (116)(117)(118)(119)(120) or without known subfertility (121); one study was restricted to men with proven fertility (122). Only in two studies were men with occupational exposure to BPA included (111,112).…”
Section: Effects On Semen Quality and Reproductive Outcomes: Evidencementioning
confidence: 99%